Learners’ Home-Based Learning Activities and Academic Achievement in Modular Learning - Haydee D. Villanueva; Carlyn V. Campos (EduLine: Journal of Education and Learning Innovation, 2022)
The new normal education requires learners to be independent in the learning process without face-to-face instruction. This study determined the home-based learning activities in relation to the academic achievement of Grade 6 learners in Plaridel North District, Municipality of Plaridel, Misamis Occidental. The descriptive-correlational design was used in the study. There were 135 students who served as respondents, selected through purposive and convenient sampling techniques. The researcher-made Home-Based Learning Activities Questionnaire was used as a research instrument in determining the learners’ learning activities at home. Documentary analysis was made to determine the learners' academic achievement. Mean, Standard Deviation, Pearson Product-Moment Correlation Coefficient, and Regression Analysis were used as statistical tools in analyzing the data gathered. Results revealed that the respondents had a very high engagement in home-based learning activities, and their academic achievement was generally very satisfactory. The level of engagement in home-based learning activities was highly influential to the learners' academic achievement. The efforts extended for modular distance learning can determine what learners can achieve academically.